Associations of low-intensity light physical activity with physical performance in community-dwelling elderly Japanese: A cross-sectional study. - Kazuhiro P Izawa; Ai Shibata; Kaori Ishii; Rina Miyawaki; Koichiro Oka (PLoS ONE, 2017)
Physical activity and physical performance relate to quality of life, mortality, and morbidity in elderly people. However, little is known about differences in physical performance related to low-intensity light physical activity (LLPA), high-intensity light physical activity (HLPA), and moderate-intensity physical activity (MPA) and how they are separated by sex in elderly populations.This study aimed to determine differences in LLPA, HLPA, MPA, and physical performance, and associations between these measures in community-dwelling elderly men and women.Physical activity and physical performance such as timed-up-and-go test, one-leg standing time, and maximum gait speed were measured in 181 community-dwelling elderly men (mean age, 75.1 ± 5.3 years) and 109 women (mean age, 73.4 ± 4.8 years) in 2013. Physical activity was classified as LLPA (1.6~1.9 METs of physical activity), HLPA (2.0~2.9 METs of physical activity), and MPA (over 3 METs of physical activity). The association between the values of these three intensities of physical activity in the participants was assessed by Pearson's correlation coefficients. Multiple linear regression analyses were used to assess the association of physical performance values with the three groups defined by accelerometer-measured physical activity intensity adjusted for sociographic, behavioral, and multiple diseases in the participants.MPA was beneficially associated with all physical performance indicators in the men (all P<0.05) and women (all P<0.05). Only HLPA showed significant associations with the timed-up-and-go test (P = 0.001) and maximum gait speed (P = 0.006) in women.These results may support the notion that not only HLPA in women but MPA in both sexes appears to improve physical performance in elderly populations.The present study findings provide novel epidemiological evidence for the potential benefits of HLPA in women and also reinforce the potential benefits of MPA in both sexes, which is the mainstay of public health recommendations.